A study on tensor product surfaces in low-dimensional Euclidean spaces - Etemad, Dehkordy A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We consider a special case for curves in two-, three-, and four-dimensional Euclidean spaces and obtain a necessary and sufficient condition for the tensor product surfaces of the planar unit circle centered at the origin and these curves to havea harmonic Gauss map.